COMPARATIVE STUDY: P2P SHARIAH CONTRIBUTION INTENTIONS BETWEEN GENERATION Z AND MILLENNIALS - Nugroho, Moh Agus; Syarif H Djauhari , Muhammad; Syawaluddin, Syawaluddin (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2024)
Introduction: Shariah-compliant P2P lending in Indonesia has significant potential but still faces major challenges, such as low financial literacy and high risk perception among Generation Z and Millennials. This study investigates factors influencing individuals' intentions and contributions to Islamic P2P Lending using the Theory ofPlanned Behavior(TPB). Methods: A sample of 202 individuals was analyzed using Partial Least Squares(PLS) to handle the complex model with latent variables and non-linear relationships. Results: This study found that attitude(AT), subjective norms(SN), and perceived behavioral control(BC) have a significant positive influence on the intention to contribute(IC) to Islamic P2P Lending, consistent with the Theory of Planned Behavior(TPB). Additionally, religiosity(RE) and intention to contribute(IC) significantly impact actual contributions(CP) to Islamic P2P Lending. The indirect effects show that attitude, subjective norms, and perceived behavioral control influence contributions through intention, with intention serving as the main mediator. The multigroup analysis reveals no significant differences between Generation Z and Millennials, suggesting that strategies to increase participation can be similarly applied to both generational groups. Conclusion and suggestion: To enhance participation in Islamic P2P Lending, it is essential to foster positive attitudes, encourage supportive social norms, and strengthen users' sense of control. The same strategies can be applied to increase participation from both Generation Z and Millennials